A bumpy gold nanostructure exhibiting DNA-engineered stimuli-responsive SERS signals. Issue 20 (11th May 2018) - Shang, Yingxu; Shi, Jia; Liu, Huan; Liu, Xinfeng; Wang, Zhen-Gang; Ding, Baoquan
Abstract : A DNA-modified bumpy gold nanostructure with built-in electromagnetic hotspots was synthesized, and the DNA conformational changes that were triggered by the external stimuli (K + /kryptofix or H + /OH − ) induced reversible on/off switching of SERS signals. Abstract : We present a SERS-active gold nanostructure with built-in electromagnetic hotspots formed by densely packed gold nanoparticles on a gold nanorod. Cy3 labeled stimuli-responsive DNA motifs were introduced to the SERS-active nanostructure. The SERS signals can be switched ON and OFF reversibly in response to external stimuli (pH, metal ions or organic molecules).